Gambaran pengetahuan, sikap, dan perilaku tentang vaginal hygiene terhadap kejadian keputihan patologis pada siswi kelas 1 di SMA Negeri 1 Denpasar periode Juli 2018 - Ida Ayu Cintya Pradnyandari; I Gede Ngurah Harry Wijaya Surya; Made Bagus Dwi Aryana (Intisari Sains Medis, 2019)
Introduction: Leucorrhea was a prolonged problem that has been experienced by women, especially teenagers. Teenagers are part of a population that are at risk. Pathological leucorrhea which is not prevented and handled properly can cause various disease and have a fatal end. This research aimed to know how were the knowledge, attitudes, and behavior of vaginal hygiene towards pathological leucorrhea phenomenon on first grade female students in 1 Senior High School of Denpasar City. Method: This research was a descriptive study with cross-sectional method. The research subject was 106 first grade female students in 1 Senior High School of Denpasar City. The data were collected on 26th of July 2018. This research used primary data from the questionnaire that had been filled out.Result: The results showed that the level of knowledge about vaginal hygiene was 99,9% good and 0,1% bad. The level of attitudes about vaginal hygiene was 100% good. The level of behavior about vaginal hygiene was 98,2% good and 1,8% bad.Conclusion: Most of the student in Senior High School 1 Denpasar have a good level of knowledge, attitude, and behavior towards vaginal hygiene.